Preventing lethal school violence - Daniels, Jeffrey A. 1965-; Bradley, Mary C.; SpringerLink (Online service). (New York Springer, 2011)
Bullying. Gang assaults. Rampage shootings. School violence, especially when it turns deadly, has enduring social and psychological effects on students, faculty, staff, and the community. And though a great deal of research focuses on the significant role children?s positive social development plays in reducing incidents of school violence, in-depth examinations of evidence-based preventive measures have remained minimal until now. With its focus on averting lethal school violence, this unique volume translates the prosocial findings into practicable preventive measures that can be put to use in school settings. Making expert use of news reports as well as scholarly data, Preventing Lethal School Violence clarifies the links between bullying and lethal violence and delineates typical characteristics of school shooters while cautioning against outright profiling. Students' awareness of self and others, strong connections with adults, and other social and ethical skills form the basis of a comprehensive, research-based model for reducing?and potentially eliminating?lethal incidents at school. This accessible volume: Outlines the scope of school violence as a broader social problem. Summarizes current information on the traits common to students who commit lethal violence at school. Examines the relationship between bullying/cyberbullying and rampage incidents. Analyzes examples of successful prevention of violent acts and resolution of hostage situations. Describes in detail the concept of positive school climate and introduces the Safe School Communities Model. Synthesizes key research data into violence prevention skills for students, teachers, administrators, and all professionals working in schools. Preventing Lethal School Violence is a must-have resource for researchers and professionals in school psychology and allied education disciplines, including school administration, school counseling, and social work.
Introduction to Lethal School Violence -- Costs of Lethal School Violence -- Bullying and Lethal Acts of School Violence -- Averted School Rampages -- Successfully Resolved Barricaded Captive Events -- Building a Positive School Climate -- The Safe School Communities Model.
Electronic reproduction.
Keywords: School violence -- Prevention; Electronic books